Peierls barriers of a-type edge and screw dislocations moving on basal and prismatic planes in magnesium - Ostapovets, Andriy; Vatazhuk, Olena (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Exact shape of Peierls barriers are calculated for edge and screw dislocation gliding on basal and prismatic planes in magnesium by using of several popular interatomic potentials. Comparison of these potentials is performed in order to describe their abilities and limitations. Stability of different types of dislocation cores are analyzed as well as their mutual transformations during dislocation slip. It was found that the Peierls stresses and barrier height are dependent on core type. It was concluded that transformations of dislocation cores along minimal energy paths have to be taken into account for development of analytical models of the slip in magnesium. The results are compared with available first-principles calculations.